Sexuality in old age: uma discussão da Aids, envelhecimento e medicamentos para disfunção erétil - Sousa, Jailson L. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Recent trends of the AIDS epidemic have been placing a new age group in evidence of the discussion about vulnerability: the elderly. With the increasing populational aging, many investments have been made to improve the quality of life of such age group; in which the population is starting to live life in its fullness, with increased social relationships and also, why not, sexual relationships - once sexual desire does not end when the peo ple get older. The marketing of medicines for erectile dysfunction in 1998 in Brazil has brought the necessity to discuss their impact in a part of the Brazilian population which is increasing intensively - the one that did not have the habit of dealing with preventive methods decades ago. Thus, this paper aims to present a review of current scientific literature, approaching the issues of sexuality in the old age, the medicines for erectile dysfunction and the increasing of cases of AIDS among the elderly people.